Synovial Osteochondromatosis at the Carpometacarpal Joint of the Thumb. (11th January 2017) - Yonekura, Satoru; Hagiwara, Hiroyoshi; Nishimura, Takahiro; Amagai, Hiroshi; Yamamura, Mayu; Miyamoto, Osamu; Nakama, Sueo
Abstract : Synovial osteochondromatosis (SOC) is a benign tumor characterized by synovial connective tissue metaplasia. SOC commonly affects major joints including the knee followed by the hip, elbow, and wrist. SOC cases in the hand are not reported as often as SOC of major joints. Particularly SOC of the carpometacarpal joint of the thumb is rare. We report on a 57-year-old female with primary SOC of the carpometacarpal joint of her left thumb. Surgical excision was performed and the patient had no symptoms with full range of motion of her left thumb. At 3 years of follow-up, there was no recurrence.